Maritime Indonesia and the Archipelagic Outlook; Some reflections from a multidisciplinary perspective on old port cities in Java - Lauder, Multamia RMT; Lauder, Allan F. (Wacana, Journal of the Humanities of Indonesia, 2016)
The present paper reflects on Indonesia's status as an archipelagic state and a maritime nation from a historical perspective. It explores the background of a multi-year research project into Indonesia's maritime past currently being undertaken at the Humanities Faculty of Universitas Indonesia. The multidisciplinary research uses toponymy, epigraphy, philology, and linguistic lines of analysis in examining old inscriptions and manuscripts and also includes site visits to a number of old port cities across the archipelago. We present here some of the core concepts behind the research such as the importance of the ancient port cities in a network of maritime trade and diplomacy, and link them to some contemporary issues such as the Archipelagic Outlook. This is based on a concept of territorial integrity that reflects Indonesia's national identity and aspirations. It is hoped that the paper can extend the discussion about efforts to make maritime affairs a strategic geopolitical goal along with restoring Indonesia's identity as a maritime nation.